Perspektywy zastosowania podejścia zasobowego w zarządzaniu strategicznym przedsiębiorstw (Prospects of Using the Resource-Based View of Strategic Management, 2008)
There are a lot of approaches to formulating strategy in the frames of strategic management (planning, competitive positioning, emergent, resource-based view). One of the most recent and popular one among both managers and scientists is the resource-based view of the strategy. According to this approach the efficiency of an enterprise depends on the possession and proper use of resources and capabilities of a company. The main goal of the article is to describe the prospects of using the resource-based view of strategic management in practice. To achieve this goal the author first presents the main trends of changes that are taking place in enterprise's environment and then compares these trends to the basic assumptions of resource-based view of strategic management.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 227-233